2006
DOI: 10.1097/01.yic.0000224785.68040.43
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with polypharmacy and excessive dosing in patients with schizophrenia treated in four European countries

Abstract: The purpose of this study was to calculate the proportion of patients with schizophrenia receiving persistent antipsychotic polypharmacy and excessive dosing in four European countries; to test the hypothesis that excessive dosing and/or antipsychotic polypharmacy is associated with higher levels of psychopathology; and to establish whether use of second-generation antipsychotics is a protective or a risk factor for polypharmacy and excessive dosing. Participants with schizophrenia were recruited from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
7
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 24 publications
9
57
7
2
Order By: Relevance
“…Internationally, the rate of polypharmacy in discharged individuals was 28% in Italy, 10 27.5% in Canada, 15 35.6% in Norway 16 and 40% in the Medicaid group in the USA, 17 all higher than what we observed. However, our finding was similar to that of Centorrino et al 18 in the USA and Barbui et al 12 in Italy where 15.8 and 13% respectively were on polypharmacy.…”
Section: 10supporting
confidence: 46%
See 1 more Smart Citation
“…Internationally, the rate of polypharmacy in discharged individuals was 28% in Italy, 10 27.5% in Canada, 15 35.6% in Norway 16 and 40% in the Medicaid group in the USA, 17 all higher than what we observed. However, our finding was similar to that of Centorrino et al 18 in the USA and Barbui et al 12 in Italy where 15.8 and 13% respectively were on polypharmacy.…”
Section: 10supporting
confidence: 46%
“…11 Studies based on patients in the community also report higher rates. A study involving four European countries observed that 28% persistently received highdose antipsychotics, 12 whereas Tungaraza et al 13 observed that 14% of their UK-based study group were similarly treated.…”
Section: Discussionmentioning
confidence: 99%
“…29 In keeping with previous studies, the PDD:DDD ratio for APP was calculated as the sum of the individual PDD:DDD ratios of all antipsychotics prescribed to a patient; high-dose prescribing was defined as a PDD:DDD of greater than 1.5. [30][31][32] In addition to antipsychotic agents, data on coprescription of anticholinergic agents, mood stabilizers, antidepressants, and benzodiazepines were captured.…”
Section: Data and Variables Extractedmentioning
confidence: 99%
“…Ho et al [38] empfehlen nach der aktuellen Studienlage, Antipsychotika nicht abzusetzen, jedoch "jedem Patienten die niedrigste Dosis (zu) verordnen, um Symptome zu kontrollieren" -und zwar bereits bei Therapiebeginn. Dies steht in Gegensatz zum auch heute noch teilweise praktizierten Vorgehen mit vergleichsweise hohen Einstiegsdosierungen, weiteren Dosissteigerungen [109] und nicht evidenzbasierter Polypharmazie im Verlauf [110,111]. Ein abnehmendes Ansprechen durch dosisabhängige Vermehrung ("upregulation"), Sensibilisierung und vermehrte Dopaminsynthese und Ausschüttung der mesolimbisch-striatalen D2-Rezeptoren kann u. a. dafür ursächlich sein [112,113].…”
Section: Therapeutische Schlussfolgerungenunclassified